Structural Analysis of Porcine Reproductive and Respiratory Syndrome Virus Non-structural Protein 7α (NSP7α) and Identification of Its Interaction with NSP9 - Chen, Jiaping; Xu, Xiaodong; Tao, Hu; Li, Yuan; Nan, Hao; Wang, Yuanyuan; Tian, Mengmeng; Chen, Hongying (Frontiers in Microbiology, 2017)
Nonstructural protein 7 (NSP7), which can be further cleaved into NSP7α and NSP7β, is one of the most conserved proteins of porcine reproductive and respiratory syndrome virus (PRRSV). NSP7 plays a role in provoking the humoral immune system in PRRSV-infected swine, but its structure and function are still not fully understood. Here, we analyzed the expression of NSP7, NSP7α and NSP7β in PRRSV-infected Marc-145 cells. The solution structure of NSP7α was determined by using nuclear magnetic resonance (NMR). Although the structure provided little clue to its function, based on the structure of NSP7α, we predicted and further identified some key amino acids on NSP7α for the interaction of NSP7α with NSP9, the RNA dependent RNA polymerase of PRRSV. This study provided some new insights into the structure and function of PRRSV NSP7.